2017
DOI: 10.1111/nep.12813
|View full text |Cite
|
Sign up to set email alerts
|

Serum sclerostin values are associated with abdominal aortic calcification and predict cardiovascular events in patients with chronic kidney disease stages 3–5D

Abstract: Serum sclerostin values are associated with the presence of AAC, but are lower when AAC is moderate to severe. Higher values are predictive of reduced short-term cardiovascular events. Taken together, these results suggest that sclerostin may have a role in the development of or the response to vascular calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
0
27
4
Order By: Relevance
“…Interestingly, despite the predictive ability of sclerostin for all-cause mortality in the current study, serum sclerostin was not associated with cardiovascular mortality, which differs from the independent relationship between sclerostin and cardiovascular mortality revealed by a previous result [ 29 ]. The discrepancy of the results may be attributable to the difference in demographic characteristics, considering that patients with chronic kidney disease were enrolled in the previous study and we focused on elderly SCAD patients with normal renal function.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, despite the predictive ability of sclerostin for all-cause mortality in the current study, serum sclerostin was not associated with cardiovascular mortality, which differs from the independent relationship between sclerostin and cardiovascular mortality revealed by a previous result [ 29 ]. The discrepancy of the results may be attributable to the difference in demographic characteristics, considering that patients with chronic kidney disease were enrolled in the previous study and we focused on elderly SCAD patients with normal renal function.…”
Section: Discussioncontrasting
confidence: 99%
“…After vascular calcification has progressed, serum sclerostin is elevated to decrease β-catenin stability in the cells and suppress the proliferation and differentiation of osteoprogenitor cells [ 15 , 16 , 37 ]. Clinical studies have reported that serum sclerostin levels are positively correlated with carotid intima-media thickness in hemodialysis patients, and positively associated with coronary artery or abdominal aortic calcification in non-dialysis CKD patients [ 40 42 ]. Moreover, serum sclerostin levels were found to be positively associated with brachial-ankle PWV values in kidney transplantation patients, and positively associated with cfPWV values in chronic kidney disease (CKD), hemodialysis, and postmenopausal women [ 20 , 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sclerostin has been reported to be involved in macrovascular development [225]. Serum sclerostin levels have also been reported to correlate with the calcification of the abdominal aorta in patients with chronic kidney disease [226]. Alternatively, there is a report that survival prognosis in dialysis patients is not correlated with serum sclerostin levels [227], and the effect of sclerostin on the vasculature is controversial.…”
Section: Future Direction and Conclusionmentioning
confidence: 99%